ANALYSIS OF BRAND EQUITY ON BUYING DECISION OF SACHETED ADEM SARI ON PT. ENESIS INDONESIA IN PALEMBANG - Zarwin, Zarwin; Sri Hartono (Dinasti Publisher, 2020)
This study aims to Analysis of Brand Equity on Buying Decision of Sacheted Adem Sari On PT. Enesis Indonesia in Palembang by measuring indicators that influence the Brand Equity variable, Consumer Decision. The population in this study are consumers who have consumed Adem Sari refresher at least 1 time based on their own decision with an age range of 19 to 50 years, so that 96 respondents were obtained to become the sample of this study. The primary data collection method is in the form of a questionnaire using a Likert scale. Data analysis methods used are validity test, reliability test, t test, f test, coefficient of determination, correlation between dimensions and multiple linear regression analysis. Based on the results of data analysis, it shows that the brand equity variable partially and simultaneously has a positive and significant influence on the purchasing decision of Adem Sari Sachet Products.